A qualitative study on mothers' experiences attending an online infant massage class: "It is funny! I feel close to my baby!" - Siti Khuzaiyah; Qorinah Estiningtyas Sakilah Adnani; Nur Chabibah; Milatun Khanifah; Ka Yiu Lee (BMC, 2022)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic impacts maternal and perinatal health. Fear of COVID-19 transmission may lead to psychological disorders among mothers, such as anxiety and depression, which might affect the infant's health. Innovation is needed to address problems related to this condition. This study aimed to explore the experiences of mothers who had attended online infant massage classes.  Methods This qualitative survey recruited 12 Indonesian mothers who had infants aged < 12 months and joined the online infant massage class. An open-ended question form was used to collect data, which were analyzed using thematic content analysis. Results There were six themes related to the experiences of mothers attending online infant massage classes: favorite session, new knowledge and skills, benefits, barriers during infant massage class, factors related to infant massage practice, and mother's hope. Conclusions Mothers had a good experience learning infant massage and had better interaction with their infants after the class. The findings show that an online infant massage class could benefit both mothers and infants.